Pemanfatan Tanaman Obat Herbal Untuk Penyakit Degeneratif Pada Kelompok Ibu-Ibu Pca Kabupaten Pekalongan - Slamet, Slamet; Muthoharoh, Ainun; Pambudi, Dwi Bagus; Fuad, Asfal; Setianto, Gigih (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Degenerative disease is a disease that usually occurs in old people. This disease accompanies the age of a person who has decreased organ function due to old age. Sick humans will try to treat minimal illnesses by utilizing plants that grow around them. The aim of this PkM is to introduce plants that are around us for the treatment of these degenerative diseases. The method used is lecture accompanied by questions and answers. The results obtained from this PkM are additional knowledge and understanding about herbal plants that can be used for the treatment of degenerative diseases such as hypertension, cholesterol, arthritis, gout and diabetes and how to make medicinal preparations. The results of understanding the material presented are measured by the results of the pre-test and post-test.